Benefits and Concerns of the Sharing Economy: Economic Analysis and Policy Implications - Min Jung Kim (KDI Journal of Economic Policy, 2019)
This paper economically analyzes the benefits and concerns of the sharing economy and derives policy implications that could help to achieve the expected benefits and respond appropriately to any concerns. Primary benefits anticipated from the sharing economy are the creation of new transactions and promotional and market testing opportunities, and the main concerns include the crowding out of existing transactions as well as transaction and social risks. How these benefits and concerns are being realized in Korea is empirically examined by conducting a survey on participation experiences with the sharing economy. The sharing economy is expected to contribute to the enhancement of social welfare with its wide range of benefits if risk factors can be properly controlled. Accordingly, an institutional framework is needed to support the stable growth of the sharing economy, and the unique characteristics of non-professional, peer-to-peer transactions should be reflected in tandem with regulatory equity between existing and sharing economy suppliers. To do this, transaction-volume-based regulations are recommended. Furthermore, to secure regulatory effectiveness and to alleviate transaction risks, the pertinent obligations must be imposed on sharing platforms.
Keywords: D16; L51; L81; M3; 330; Sharing Economy; Peer-to-peer (P2P) Transaction; Non-professional Supplier; Regulatory Equity